Suicidal behaviors are associated with loneliness and decrease during inpatient CBASP treatment for persistent depressive disorder. (October 2022) - Wolf, Johannes; Padberg, Frank; Nenov-Matt, Tabea; Amann, Benedikt L.; Barton, Barbara B.; Tang, Jeni; Glessner, Gloria; Brakemeier, Eva-Lotta; Jobst, Andrea; Musil, Richard; Reinhard, Matthias A.
Abstract: Suicidal ideation and behavior (SIB) are common in persistent depressive disorder (PDD) and may be related to interpersonal dysfunction. While SIB has been extensively analyzed in other high-risk disorders (e.g., borderline personality disorder, BPD), data on interpersonal risk factors and effects of specific psychotherapy on SIB in PDD are limited. This study aimed at investigating loneliness versus social network size as interpersonal risk factors for SIB in PDD and assess effects of cognitive behavioral analysis system of psychotherapy (CBASP) on this domain. In a prospective naturalistic study, 64 PDD patients were assessed, who underwent a 10-weeks inpatient CBASP program. Our clinical comparison group consisted of 34 BPD patients, who underwent a 10-weeks inpatient dialectical behavioral therapy (DBT) program. SIB was measured with the Columbia-Suicide Severity Rating Scale (C-SSRS), loneliness and social network size with the UCLA Loneliness Scale (UCLA) and the Social Network Index (SNI). Twenty-six PDD patients (40.6% of the PDD sample) showed current SIB at baseline in comparison with 26 BPD patients (76.5% of the BPD sample). While in suicidal PDD patients, SIB was associated with perceived social isolation (UCLA), but not with reduced social network size (SNI), this association was not observed in suicidal BPD patients. In PDD, SIB significantly decreased during CBASP. In conclusion, SIB appears to be associated with interpersonal factors related to loneliness in PDD, but not in BPD. CBASP showed first positive evidence in reducing SIB in PDD, but our pilot data need replication studies. Highlights: Suicidal behaviors were associated with loneliness but not with social network size. This association was observed in persistent depressive disorder. We found no such associations in borderline personality disorder. CBASP showed first positive evidence in reducing suicidal behaviors.